Penyuluhan Tentang Pencegahan Stroke Kepada Pasien Dan Keluarga Pasien - Lina Wati Novikasari; Prima Dian Furqoni; Djunizar Djamaludin; Triyoso Triyoso; Shandy Aulia Wiratama (Jurnal Perak Malahayati: Pengabdian Kepada Masyarakat, 2026)
Introduction: Stroke is a sudden disruption of brain function caused by blocked blood flow or rupture of blood vessels in the brain, which may lead to disability or death. Health promotion is important to prevent stroke.Objective: This community service activity aimed to improve patients’ and families’ knowledge regarding stroke prevention.Method: The activity was conducted through face-to-face counseling using lectures, discussion, leaflets, banners, and projector media. Participants were patients and families in Siger Ward, RSUD Dr. A. Dadi Tjokrodipo. The activity was conducted on January 09, 2026.Results: The majority of participants were female, accounting for 9 people (60.0%). Before the counseling activity, most participants had moderate knowledge, with 7 people (46.7%), while only 3 people (20.0%) had good knowledge. After the health promotion activity, participants’ knowledge increased, with 13 people (86.7%) having good knowledge, and no participants remaining in the poor knowledge category.Conclusion: Health education on stroke prevention was carried out successfully and had a positive impact on improving participants’ knowledge.Keywords: counseling, health promotion, stroke